The Product Manager's Toolkit Methodologies, Processes and Tasks in High-Tech Product Management - Steinhardt, Gabriel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Product management is challenging, complex, and often misunderstood. Across the high-tech industry, drastically different duties and responsibilities are attributed to product management professionals. Diverse interpretations regarding the role of product management have only further confused practitioners and stifled the ability to develop clear and consistent product management methodologies. "The Product Manager$1 (Bs Toolkit" book provides a consistent and holistic managerial approach to product management and presents a practical and comprehensive methodology (tasks, processes, deliverables, and roles) that covers nearly all aspects of product management.s
Product Management Concepts -- Who$1 (Bs Driving Your Company? -- Product Management Team -- Product Definition Team -- Crafting Market Requirements -- Concept of Marketing -- Value-Marketing Model -- Extending Product Life Cycle Stages -- Product Management Glossary -- Product Manager's Toolkit -- PMTK Introduction -- PMTK Models -- PMTK Templates.s
Keywords: Economics; Marketing; Business planning; Technology; Economics/Management Science; Organization/Planning.; Marketing; Technology Management